Disability and gender inequality, the disadvantage for women - Miguel Ángel Karam Calderón; Yazmín Castillo Sánchez; Pablo Moreno Pérez (Social Medicine Publication Group, 2020)
In the field of health, it is considered that the gender perspective should start from the recognition of the deep inequalities of health based on gender. Gender, as a social construction, is a very important factor, which increases biological vulnerability and accompanies biology in determining health inequalities. Being a man or a woman favors health differences and these are significant within any socioeconomic group, and especially when it comes to women with disabilities. There is little literature in Latin America and particularly in our country about the inequality status of women with disabilities, however, the data obtained makes clear reference to the fact that women with disabilities occupy a lower status in our society, finding themselves in a situation of enormous social, economic, educational and professional disadvantage. Therefore, in this work it is intended, through the review based on secondary sources, to carry out an analysis that allows the integration of the gender perspective with the social conception of disability, for the understanding of inequality in our societies and the elaboration of strategies to redefine social relations in fairer and more equitable terms and a notion of citizenship that includes everyone, transcending from the hegemonic reductionist vision of medicine to a broader and more inclusive vision.